If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + -12x + 18 = 33 Reorder the terms: 3 + 18 + -12x = 33 Combine like terms: 3 + 18 = 21 21 + -12x = 33 Solving 21 + -12x = 33 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + -12x = 33 + -21 Combine like terms: 21 + -21 = 0 0 + -12x = 33 + -21 -12x = 33 + -21 Combine like terms: 33 + -21 = 12 -12x = 12 Divide each side by '-12'. x = -1 Simplifying x = -1
| 9x-10y=24 | | -4-8=4(-3n+2) | | 9x-11=3x+8 | | 4x(3-y)=0 | | x+5(x-2)=8 | | 24+3x=3x(7-1) | | 9n+1=10 | | 10x=2+5 | | X-0.2x=520 | | 6x+29=-25 | | f(x)=x-(3/lnx) | | f(x)=x-3/lnx | | 18x-5x+4=28 | | 8x-(6x+5)=4x-21 | | 4x+2=(x-5) | | 4y+2=3(y-5) | | 3(3+3x)=8(x-2) | | 3(3+3)=8(x-2) | | 6x/2-3 | | 7*7*7*7*7=212 | | 7*5=212 | | 3t-9=7-1 | | 6x+3y=15.75 | | 7z-5-5(z+1)=-(4z+7) | | 1/3*4x | | 2k^2+7k-30=0 | | 7-q/4=2.5 | | 7-4=2.5 | | -3x+10y=0 | | sx+ty=ufory | | 8v=-18 | | 4lnx+6=0 |